Pain Response in the First Trimester after Percutaneous Vertebroplasty in Patients with Osteoporotic Vertebral Compression Fractures with or without Bone Marrow Edema - Voormolen, M.H.J.; van Rooij, W.J.; Sluzewski, M.; van der Graaf, Y.; Lampmann, L.E.H.; Lohle, P.N.M.; Juttmann, J.R. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Presence of bone marrow edema (BME) in osteoporotic vertebral compression fractures (VCF) detected by MR imaging as selection criterion for percutaneous vertebroplasty (PV) is speculative. To clarify significance of BME in VCF, we assessed pain response after PV in patients with VCF with full BME versus patients with VCF with absent BME.METHODS: From a cohort of patients with painful VCF selected for PV, pain response in 14 patients with absent BME in VCF was prospectively compared with pain response in 31 patients with full BME in VCF. Pain was evaluated before PV and at 1 and 3 months after PV with visual analog scores and analgesics used. Back pain in general and at treated vertebral levels was assessed.RESULTS: Pain decrease after PV at treated levels was observed in 10 (71%) patients with absent BME in VCF at both follow-up periods and in 29 (94%) patients with full BME 1 month after PV and 30 (97%) at 3 months after PV. Differences between the groups were significant (P = .04 at 1 month; P = .01 at 3 months). Pain response was not affected by other patient or imaging characteristics. General back pain after PV was comparable in both groups after PV (P = .08 at 1 month; P = .4 at 3 months).CONCLUSION: Pain decrease after PV in patients with VCF is more frequently observed when full BME is present. Because 71% of patients with VCF with absent BME responded favorably on pain, PV should not be withheld based on absence of BME alone.